(untitled) (LEARNing Landscapes, 2008)
This paper examines the experience of being a researcher and how this experience shapes who we are in a process of mutual shaping. The very engagement with research, the author suggests, parallels the engagement with music and the arts. In this engagement, problem setting and problem solving, the conceptual and the embodied, the analytic and the holistic, are interconnected and interdependent. Assuming the role of an animator, the communication of the research intensifies our engagement, contributing to the shaping of who we are.